Maximizing the adequacy of Hologic® Cervista® HPV HR results on ThinPrep® Pap samples treated with glacial acetic acid. Issue 3 (18th January 2016) - Mahajan, Aparna; Kucher, Erek; Hoefle, Wanda; Engelhardt, Shawna; Accola, Molly; Barasch, Samuel; Rehrauer, William; Selvaggi, Suzanne M.
Abstract : Background: Although glacial acetic acid (GAA) treatment of bloody cervical samples has reduced the rate of unsatisfactory Pap Tests, recent studies suggest that it may negatively impact high‐risk (hr)‐HPV test results. The objectives of this study were to compare the levels of genomic DNA between GAA treated and nontreated ThinPrep ® samples using the Hologic ® Cervista ® HPV‐HR assay and to compare the adequacy of the ThinPrep ® Pap Test between aliquoted and nonaliquoted samples. Methods: Prior to GAA treatment, 2.5 ml of the cervical sample was prealiquoted from 102 bloody ThinPrep ® vials. Both GAA treated and nontreated samples were analyzed for hr‐HPV using the Cervista ® HPV HR assay. The levels of genomic DNA were measured and compared between these samples. In addition, ThinPrep ® Pap Test adequacy rates were calculated and compared on aliquoted and nonaliquoted cervical samples. Results: Of the 102 cervical samples, 95 (93%) nontreated aliquots contained satisfactory levels of genomic DNA as compared to 36 (35%) GAA‐treated samples ( p  < 0.00001). Ninety‐nine (97%) aliquoted cervical samples were satisfactory for cytologic evaluation as compared to 1, 326 (96%) GAA treated samples from 2013 (nonaliquoted); not statistically significant ( p  = 0.7968). Conclusion: The levels of genomic DNA were significantly decreased in GAA treated vs non‐treated TP samples. Aliquoting from the TP sample prior to treatment with GAA enables accurate measurement of DNA without affecting the adequacy of the TP cytology slide. Diagn. Cytopathol. 2016;44:215–219. © 2016 Wiley Periodicals, Inc.